PELAKSANAAN PELAYANAN DI KANTOR CAMAT KUBU KABUPATEN ROKAN HILIR - Rauzanah "; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The implementation function is an effort to create a climate of cooperation among the staff of program implementation so that the organization's goals can be implemented effectively and efficiently. The function of execution and supervision is the most important management function in a management process. Public service or public service can be defined as any form of services, either in the form of public goods or public services which in principle become the responsibility and implemented by the Government agencies at the Central, in the Region, and within the State-Owned Enterprises or Regional Owned Enterprises , in order to meet the needs of the community as well as in the implementation of the provisions of legislation. In this study the authors use the theory of Budiman in L.P Sinembela (2016) consisting of Reliability, Tangibles, Responsivenes, Assurance, Empathy. The type of research is descriptive qualitative research method. This research was conducted at the Office of the Head of Kubu Regency of Rokan Hilir Regency. Techniques of collecting data through interviews, observation, and documentation. Data analysis used qualitative descriptive method. The results of this study indicate that the Implementation of Service in the Office of the Sub-District Kubu Rokan Hilir in the management of correspondence is not optimal. It means that human resources are still classified as less. In addition the facilities and infrastructure needed is still inadequate, so that in the correspondence not in accordance with the time specified.Keywords: Implementation, service, human Resources